Finding connections between spirituality and play for early childhood education. Issue 1 (2nd January 2019) - Mata-McMahon, Jennifer
ABSTRACT: In an attempt to provide holistic education and care, expand the view of young children's development to include the spiritual, and make connections with the found benefits of play for all areas of development, this article looks at 33 surveyed U.S. early childhood educators' perceptions on nurturing spirituality through open-ended and free play. Data collected from the open-ended questions of an online survey were analyzed looking at 22 mentions of play as a mean to support spirituality. Findings show that 45.5% of surveyed teachers mentioned play as a way intentionally used in the classroom to nurture children's spirituality. It is posed that developmentally appropriate approaches to early childhood education would be enhanced by including spirituality in their understanding of the child, as well as intentionally nurturing spirituality in educational settings, by providing free, child-centered, child-directed play and opportunities for children to experience spiritual moments, defined as feeling wonder, awe, joy, and inner-peace.